Hangover double feature - Cooper, Bradley; Phillips, Todd 1970-; Cooper, Bradley; Helms, Ed; Galifianakis, Zach (Burbank, CA Warner Bros. Entertainment, 2015)
Doug and his groomsmen head to Vegas for his bachelor party, but when they wake up the next morning with the worst hangovers they have ever had, they realize Doug is missing and no one can recall the events of the past twelve hours; Stu and his groomsmentravel to Thailand for his wedding ceremony, and his plans for a pre-wedding brunch suddenly go awry.
The hangover (2009, 100 min.) / produced by Todd Phillips, Dan Goldberg ; written by Jon Lucas, Scott Moore ; directed by Todd Phillips -- The hangover part II (2011, 102 min.) / produced by Todd Phillips, Dan Goldberg ; written by Craig Mazin, Scot Armstrong, Todd Phillips ; directed by Todd Philips.
Originally released as motion pictures in 2009 & 2011
Dolby digital 5.1, anamorphic wide screen 2.4:1
Features: The hangover part II: gag reel
DDC
DDSE
DDW
Keywords: Bridegrooms -- Drama; Bachelor parties -- Drama; Recollection (Psychology) -- Drama; Weddings -- Drama; Comedy films; Drama; Feature films; Fiction films; Video recordings for the hearing impaired